Carbon Capture, Utilization and Storage (CCUS): barriers, enabling frameworks and prospects for climate change - Bassam Fattouh (Oxford Energy Forum: A Quarterly Journal for Debating Energy Issues and Policies, 2022)
Carbon capture and storage (CCS) involves the trapping of man-made CO2 underground to avoid its release into the atmosphere. Because of the scale with which it could be applied, CCS is identified as a critical technology to reduce CO2 emissions to achieve global climate goals. The Intergovernmental Panel on Climate Change (IPCC) shows that most of the 1.5°C pathways assume significant use of CCS. For some energy-intensive hard-to-abate sectors such as steel and cement, technical options to reduce emissions without CCS are currently limited. CCS could reduce the cost of meeting climate targets as other sectors would otherwise have to pursue more expensive mitigation options. The Joint G20 Energy–Climate Ministerial Communiqué on July 2021 acknowledges the important role of carbon capture, utilization and storage (CCUS) recognizing 'the need for investment and financing for advanced and clean technologies, including CCUS/Carbon Recycling' urging 'all members to formulate such long-term strategies that set out pathways consistent to achieve balance between anthropogenic emissions by sources and removal by sinks'. This issue of the Oxford Energy Forum examines the recent trends in CCUS and explores the regulatory and commercial barriers limiting the deployment of CCUS at a large scale. It gathers the thoughts of many leading researchers in the field of CCUS, on its business models, and the incentive schemes and regulatory frameworks surrounding it. ~The Forum also gathers views from a number of the key countries and regions including the EU, Norway, the UK, the Netherlands, Saudi Arabia, China and Canada.
Keywords: 330